Waste heat recovery from engine coolant on mild hybrid vehicle using organic Rankine cycle. (September 2019) - Mansour, Charbel; Bou Nader, Wissam; Dumand, Clément; Nemer, Maroun
Considerable efforts have been invested in the automotive industry on electrified powertrains in order to reduce passenger cars' dependence on fossil fuels. Powertrains electrification resulted in a wide range of mass-production hybrid vehicle models, ranging from micro-hybrid, to mild, full, and battery-extended hybrids such as plug-in and range-extender electric vehicles. Fuel savings of these powertrains strongly rely on the energy management strategy deployed on-board, as well as on the technology used to recover the waste heat energy. This paper investigates the fuel savings potential of a mild hybrid vehicle using an organic Rankine cycle for generating electricity from the engine-coolant circuit. The net mechanical power and electrical power generated from the organic Rankine cycle are determined based on experimental data recorded on a 1.2-L turbocharged engine. The coolant temperature is regulated at 85°C and 105°C depending on the engine load. The R-1234yf organic fluid is used and the Rankine operating pressure has been controlled to maximize the overall system efficiency under technological constraints. The dynamic programming control is used as a global optimal energy management strategy in order to define the best strategy for the engine operation and power-split between the electric and thermal paths of the powertrain. A sensitivity analysis is also performed to find the optimal size of the electric motor while taking into account the additional weight of the organic Rankine cycle system. Results show 2.4% of fuel economy improvement on The Worldwide Harmonized Light Vehicles Test Cycles.